2021
DOI: 10.1016/j.lanwpc.2021.100122
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the COVID-19 pandemic on health services utilization in China: Time-series analyses for 2016–2020

Abstract: Background The aim of this study is to quantify the effects of the SARS-CoV-2 pandemic on health services utilization in China using over four years of routine health information system data. Methods We conducted a retrospective observational cohort study of health services utilization from health facilities at all levels in all provinces of mainland China. We analyzed monthly all-cause health facility visits and inpatient volume in health facilities before and during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
157
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(173 citation statements)
references
References 53 publications
14
157
1
1
Order By: Relevance
“…Secondly, although the inclusion/exclusion criteria for the testing stayed the same during the pandemic, the total number of tests did decrease, and the profile of people who seek medical assistance for acute diarrhea might has shifted owing to the changed healthcare-seeking behavior during the COVID-19 pandemic, especially only the outpatients were enrolled in this surveillance. National health facility visits were estimated to decrease by about 23•9% in China from January to June 2020, indicating influence from the behaviors changes for patient and provider, suspension of health facilities or their non-emergency services, and massive mobility restriction, which were also influenced by the potential reduction in the risk of non-SARS-COV-2 diseases [36] . However, the reasons underlying the observed decrease in positive detection for enteric pathogens are complicated, which warrant further investigations to measure in a precise multi-factorial manner.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, although the inclusion/exclusion criteria for the testing stayed the same during the pandemic, the total number of tests did decrease, and the profile of people who seek medical assistance for acute diarrhea might has shifted owing to the changed healthcare-seeking behavior during the COVID-19 pandemic, especially only the outpatients were enrolled in this surveillance. National health facility visits were estimated to decrease by about 23•9% in China from January to June 2020, indicating influence from the behaviors changes for patient and provider, suspension of health facilities or their non-emergency services, and massive mobility restriction, which were also influenced by the potential reduction in the risk of non-SARS-COV-2 diseases [36] . However, the reasons underlying the observed decrease in positive detection for enteric pathogens are complicated, which warrant further investigations to measure in a precise multi-factorial manner.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, detailed monthly data were used, which included data for previous years, for the year the pandemic started, and even for the periods after the various waves of the pandemic. These analyses show that RHIS data are of great significance for timely and effective tracking of the performance of the health system in low- and middle-income countries [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…In South Korea, a study reported that 73.2% of study participants in that country avoided using health services during the pandemic [22]. On the other hand, in China, hospital visits for any cause fell by 51% after the COVID-19 pandemic [23]. These figures indicate that the non-utilization of health services is a problem that can probably be affecting most low-and middle-income countries worldwide due to the pandemic.…”
Section: Discussionmentioning
confidence: 99%